Réponses

2013-02-08T19:59:51+01:00

au debut j'ai changer les lettres mais c'est pas grave ca ne change rien. 
3x+3 = 3(x+1)

9x+9=3(3x+3)

4-4x = 2(2-2x)

1,2 + 1,2x = 1,2 (1+x)

4x+8=4((x+2)

7+21x= 7(1+3x)

2-16x=2(1-8x)

y2+8y = y(y+8)

8x+12y=4(2x+3y)

49a - 56b = 7(7a-8b)

15zy+30zt=15(zy+2zt)

25z2y - 15zy2 = 5z( 5zy-3y)

2y2+8y= 2y(y+4)
18z2 -27yz-3zy2 = 3zy(6z-9z-y)

a2-b2 = (a+b)(a-b)

 

a)      a(a-b)+b(a-b)

         a2-ab+ab-b2 

c) identité remarquable (a-b)(a+b) 

2013-02-08T20:20:22+01:00

3x+3 = 3(x+1)

9x+9=3(3x+3)

4-4x = 2(2-2x)

1,2 + 1,2x = 1,2 (1+x)

4x+8=4((x+2)

7+21x= 7(1+3x)

2-16x=2(1-8x)

y2+8y = y(y+8)

8x+12y=4(2x+3y)

49a - 56b = 7(7a-8b)

15zy+30zt=15(zy+2zt)

25z2y - 15zy2 = 5z( 5zy-3y)

2y2+8y= 2y(y+4) 18z2 -27yz-3zy2 = 3zy(6z-9z-y)

a2-b2 = (a+b)(a-b)

 

a)      a(a-b)+b(a-b)

         a2-ab+ab-b2 

c) identité remarquable (a-b)(a+b)